Dicarabrol, a new dimeric sesquiterpene from Carpesium abrotanoides L. Issue 19 (1st October 2015) - Wang, Jun-Feng; He, Wei-Jun; Zhang, Xiao-Xiao; Zhao, Bi-Qing; Liu, Yong-Hong; Zhou, Xiao-Jiang
Graphical abstract: Abstract: A new dimeric sesquiterpene, dicarabrol (1 ), together with three known sesquiterpenes, carabrol (2 ), 11(13)-dehydroivaxillin (3 ), and 2-desoxy-4- epi -pulchellin (4 ), were isolated from the whole plant of Carpesium abrotanoides L. Their structures were elucidated on the basis of spectroscopic analysis, and single crystal X-ray diffraction analysis. Compound1 possessed a dimeric sesquiterpene core featured with a cyclopentane ring connecting two sesquiterpene lactone units rarely discovered in nature. Dicarabrol (1 ), as well as three known sesquiterpenes (2 –4 ), had potent in vitro cytotoxicities against the K562, MCF-7, Hela, DU145, U937, H1975, SGC-7901, A549, MOLT-4, and HL60 cell lines with IC50 values ranging from 0.10 to 46.7 μM, while they showed significant antiviral (H1N1 and H3N2) activities. Furthermore, compounds1, 3 and4 displayed significant antimycobacterial activity (IC50 3.7, 6.0, and 7.6 μM, respectively).